(untitled) (Revista de Investigaciones Universidad del Quindío, 2016)
Viruses as infectious agents that every day is involved in the pathophysiology of an unlimited number of Chronic Diseases. These diseases exhibit a broad clinical spectrum, ranging from mental illness , obesity, chronic fatigue syndrome , diabetes mellitus and cardiovascular disease . In this review article one effort was made to collect updated information from the different viral agents involved in the genesis of chronic diseases, as well as possibly involved pathophysiological mechanisms in the development of these diseases after infection viral of both animals and humans.